Comparison of inhibitory effects and mechanisms of lactonic sophorolipid on different pathogenic bacteria - Ma, Xiao-jing; Wang, Tong; Zhang, Hui-min; Shao, Jun-qian; Jiang, Mei; Wang, Huai; Zhu, Hui-xia; Zhou, Dong (Frontiers in Microbiology, 2022)
Sophorolipids (SLs) in lactonic form have been proved to have different inhibitory effects and mechanisms on different pathogenic bacteria. However, systematic comparative studies among various bacteria by using pure lactonic sophorolipid (LSL) are few. This study investigated the antibacterial effects and mechanisms of LSL on four common pathogenic bacteria of Staphylococcus aureus, Lactobacillus sp, Pseudomonas aeruginosa and Escherichia coli. Indices of bacteriostatic circle, antibacterial rate, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were selected to evaluate the antibacterial effects of LSL on different pathogenic bacteria. Ultrastructural observation, cell membrane permeation analysis, intracellular ATP content determination and extracellular ultraviolet substance absorption detection were used to speculate the antibacterial mechanisms of LSL. The results showed that LSL had different inhibitory effects on different pathogens. With MIC and MBC values of 0.05 and 0.20 mg/ml, LSL performed the best inhibitory effects on S. aureus, then on P. aeruginosa, and there was no significant inhibitory effect on E. coli and Lactobacillus sp. LSL achieved the purpose of inhibiting/killing on S. aureus and P. aeruginosa by destroying bacterial cell wall, increasing the permeability of cell membrane and leading the flow-out of intracellular contents. Yet it was worth noting that even the antibacterial sites of LSL were located both in the cell wall and cell membrane of the two bacteria, the action mode and intensity were remarkably different. LSL performed a greater influence on cell membrane of S. aureus by “leaking”, while exhibited a stronger impact on cell wall of P. aeruginosa by “blasting”. These observation and investigation can help to better understand the mechanisms between LSL and different bacterial cell structures. Furthermore, the obtained results endorsed the conclusion that LSL might can be used for targeted treatment of special pathogenic bacteria.